Aqueous Energy Storage Device Based on LiMn2O4 (Spinel) Positive Electrode and Anthraquinone‐Modified Carbon‐Negative Electrode. Issue 10 (15th August 2019) - Hanna, Ortal; Malka, David; Luski, Shalom; Brousse, Thierry; Aurbach, Doron
Abstract : This article describes the design and tests of aqueous hybrid energy‐storage devices based on activated carbon‐negative electrode and LiMn2 O4 (spinel) positive electrode. For this study, activated carbons from two different sources are selected and are further improved by grafting with electroactive anthraquinone molecules. The electrolyte solution is aqueous 1 m Li2 SO4 with pH = 7.5. The performances of balanced hybrid devices are characterized by cyclic voltammetry and galvanostatic measurements. It is possible to charge the hybrid cells up to 1.5 V and cycle them with current densities of 40 mA g −1 (mass of positive electrode). These fully balanced cells can achieve thousands of cycles with capacities up to 75 mAh g −1 . Preliminary calculations predict that such devices may reach energy density approaching 35 Wh kg −1 (total mass of active materials in both electrodes). Herein, a model of "rocking chair"‐type hybrid systems, comprising carbon anodes with amplified capacity, in which the electrolyte solution can serve as a thin layer of ion carrier, is presented. It is believed that the concept may be extended to the more important Na ions hybrid cells. Such systems may be suitable for load‐leveling applications and large stationary energy‐storage devices operating with very safe aqueous electrolyte solutions. Abstract : Aqueous hybrid energy‐storage devices are presented. The positive electrode is based on a LiMn2 O4 spinel. For the negative electrodes, activated carbon improved by grafting of anthraquinone is used. A specific energy density of 35 Wh kg −1 (electrodes' mass) is achieved. These cells are fast and durable, with low hysteresis technology. Therefore, they are suitable for large energy–storage application.